The effectiveness of different grass types for pollutants removal in level spreader system - Sinang, Som Cit (2006)
Water is one of the most essential elements for human and other organisms. However, water pollution has become a serious problem and gives bad impact on human health. Stormwater runoff and sullage water from urban areas have been recognised as some of the main sources that contribute to the water pollution in the receiving waters such as rivers and lakes. Level spreader system is one of the best management practices used to reduce pollutants in urban runoff and domestic wastewater before entering the receiving watercourse. In this study, field grass and carpet grass were used to identify their efficiency for pollutants removal in level spreader system. Laboratory analysis results shows level spreader with carpet grass as vegetative strip is more effective in pollutants removal. It can remove approximately 45% turbidity, 52% TSS, 43% oil and grease, 35% ammoniacal nitrogen, 28% zinc and 22% nickel. Carpet grass is more effective because it grows in higher density than field grass, thus providing more surface area for treatment mechanism to take place. Besides that, analysis of grass samples shows that plant uptake mechanism contributes to the pollutants removal in level spreader system. Carpet grass is able to take up more pollutants than the field grass.